A tunable lanthanide cubane platform incorporating air-stable radical ligands for enhanced magnetic communication. Issue 1 (December 2018) - Brunet, Gabriel; Hamwi, Milad; Lemes, Maykon; Gabidullin, Bulat; Murugesu, Muralee
Abstract The unique properties of polynuclear cluster-aggregates have long been staples in the molecular magnetism community. The initial success observed in high nuclearity transition metal complexes for generating exciting magnetic behaviors however, has not yet fully been extended to lanthanide-based clusters. This is in part due to the challenges related to promoting non-negligible magnetic interactions between two lanthanide ions. One promising route towards improving magnetic communication involves the incorporation of radical species. Here, we describe the preparation of tetranuclear [Dy4 (μ 3 -OH)4 ]8+ core structures that allow the incorporation of air-stable radical ligands. This combination paves the way for magnetically relevant lanthanide cubane cluster-aggregates capable of strong magnetic communication and improved spin-reversal barriers. Moreover, we show that the addition of electron donating groups lead to non-negligible antiferromagnetic coupling between the DyIII centers and the BPyTz− ligands, while also simultaneously improving the slow magnetic relaxation dynamics in the absence of an applied field. The lanthanide cubane is an interesting motif for the design of magnetic molecules but typically exhibits weak magnetic exchange between ions. Here the authors report the synthesis of lanthanide cubanes incorporating air-stable radical ligands, and subsequent enhancement of intramolecular magnetic coupling.